Extended Cr-51 RBC combined with Tc-99m RBC for the detection and localisation of occult GIT bleeding - Modebe, Emmanuel Obinna (Stellenbosch : Stellenbosch University, 2014)
Thesis (MMed)--Stellenbosch University, 2014.